MIXDesign, tangible mixed reality for architectural design - Dias, J. M. S. (2022)
MIXDesign, provides a tangible Mixed-Reality system oriented towards tasks in Architectural Design, in several! usage scenarios, such as Conceptual Design, Client Brief, or even Architectural Design education. With MIXDesign, an architect can intuitively interact with a real scale model of the design, in normal working settings, where he can observe an enhanced version of the scale model, with JD virtual objects registered to the real ones. The architect is then able to use intuitive tangible interfaces, such as a paddle, to choose menu options, select a JD virtual object, transport a virtual object within the scale model surroundings, and geometrically transform an object (by rotation or scaling). MIXDesign provides a platform for testing new design concepts while seamlessly transporting the Architect from Reality (RE) to Augmented Reality (AR) and then through Augmented Virtuality (AV), towards a full Virtual Environment (VE), and back, where he can perceive and judge both the virtual and the real models, interactively and in real-time.